Moderasi BeragamMadrasah: Studi Tentang Penguatan Komitmen Kebangsaan Pada Siswa Madrasah Aliyah Negeri 1 Pangkalpinang - Yatemi Yanti (Magister Pendidikan Agama Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The spirit of national commitment that has been built in MAN Pangkalpinang still needs strengthening. It can be seen that there is still a gap between the ideals initiated by the government, especially in terms of strengthening national commitment, and what happens in the education process and does not reflect the value of national commitment. The purpose of this study is to describe how national commitment is implemented as part of strengthening religious moderation and describe the efforts of MAN 1 Pangkalpinang in order to strengthen national commitment in students. The method used is qualitative with a phenomenological approach, using descriptive analysis that focuses on the object of strengthening the value of national commitment that is studied in depth to reveal the reality in the field. The findings demonstrated that MAN 1 Pangkalpinang's national commitment initiative has been operational, but that some components still require reinforcement to instill a sense of national commitment in students. MAN 1 Pangkalpinang's efforts in strengthening the value of national commitment include, in addition to equalizing the perception of religious moderation, the need to build attitudes of national commitment in students, monitoring the use of cellphones, and being exemplary. This is the essence of strengthening national commitment, which is expected to build a nationalist, tolerant spirit and open the horizons of thinking of the millennial generation in attitude and opinion as an embodiment of Islam as a religion that is rahmatan lil alamin.